The Impact of Firm Characteristics on Earnings Management (An Empirical Study on Insurance Companies Listed in the Damascus Securities Exchange) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The study aims to examine whether insurance companies listed in the Damascus Securities Exchange practice earnings management or not. As well as to test the impact of company characteristics such as profitability, size, and leverage on earnings management measured by discretionary accruals according to the modified Jones model. To achieve this goal, secondary data was collected from the annual financial reports of the insurance companies listed in the Damascus Securities Exchange available on the official website of the market. The number of these companies was (6) during the period from 2016 to 2022, with a total of (42) observations, which were analyzed using SPSS 20 software.      The study revealed that 79% of the observations for insurance companies listed in the Damascus Securities Exchange had practiced earnings management during the study period. The results indicated a statistically significant impact of both company profitability and size on earnings management, while there was no statistically significant impact of  leverage on earnings management.